Telling Tales of Water Journeys With Isotopic Tracers - Gerbrand Koren (Water Resources Research)
Abstract Determining the sources of water inside plants using its isotopic composition is a long‐standing research challenge in ecohydrology. A better understanding of water sources can help improve models and ultimately contribute to more accurate forecasts of water availability, food production, carbon sequestration or ecosystem status. Over the years, several methods have been developed and applied to water source partitioning, and Gai et al. (2023, https://doi.org/10.1029/2022wr033849) provide a systematic assessment of the uncertainty of different isotopic tracers (2H, 3H, 17O, 18O) and mixing models (IsoSource, SIAR, MixSIR, MixSIAR) for an apple tree orchard on the Loess Plateau in north‐central China. For that study area, the combination of 2H and 18O with the MixSIAR mixing model is recommended. Importantly, the systematic assessment provides a framework that can be applied to select a suitable combination of tracers and mixing models for different ecosystems and climate zones. This commentary aims to provide a wider context for a selection of key results from Gai et al. (2023, https://doi.org/10.1029/2022wr033849) and highlight potential future research directions.